2021
DOI: 10.1002/hep.31988
|View full text |Cite
|
Sign up to set email alerts
|

Familial Hypobetalipoproteinemia: An Underrecognized Cause of Lean NASH

Abstract: amilial hypobetalipoproteinemia (FHBL) is an autosomal codominant genetic disorder characterized by over 60 different mutations in the apolipoprotein B (APOB) gene, consequently leading to translation of truncated apolipoprotein B proteins apoB-100 and apoB-48. (1) These mutations attenuate the liver's ability to export lipoproteins, thereby resulting in triglyceride accumulation. (1) As a result, FHBL is associated with the development of NAFLD as well as increased risk of NASH, hepatic cirrhosis, and HCC. (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Compared with healthy controls, lean subjects with NAFLD have increased IR, metabolic comorbidities, visceral adiposity,39,272 and decreased muscle mass. Alcohol use and alterations in the gut microbiome may also contribute to NAFLD in lean individuals 178,273–277…”
Section: Nafld In Lean Individualsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with healthy controls, lean subjects with NAFLD have increased IR, metabolic comorbidities, visceral adiposity,39,272 and decreased muscle mass. Alcohol use and alterations in the gut microbiome may also contribute to NAFLD in lean individuals 178,273–277…”
Section: Nafld In Lean Individualsmentioning
confidence: 99%
“…Genetic factors likely play a significant role in this population, but the overall genetic contribution to NAFLD requires further study 39,178,272–274. Lean individuals with NAFLD are more commonly of Hispanic or Asian origin, which is likely in part driven by a higher prevalence of the PNPLA3 I148M polymorphism 266,274,278.…”
Section: Nafld In Lean Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous missense variants of APOB gene are associated with autosomal‐dominant familial hypercholesterolemia‐2 (OMIM #144010), characterized by severely elevated LDL cholesterol levels, 10 while truncating pathogenic variants are associated with familial hypobetalipoproteinemia (FHBL), an autosomal codominant genetic disorder characterized by low total and LDL cholesterol plasma levels. Heterozygous carriers of APOB ‐FHBL have an increased risk to progress from NAFLD to NASH, fibrosis and cirrhosis, particularly in the presence of triggering factors such as excessive caloric or alcohol intake 11 . Moreover, somatic mutations in APOB frequently occur during hepatic carcinogenesis and rare APOB gene variants are enriched in NAFLD‐HCC patients 2 …”
Section: Methodsmentioning
confidence: 99%
“…74 High incidence of hepatic steatosis, liver cirrhosis, and hepatocarcinoma have been observed in individuals with FHBL attributed to mutations in APOB. 75 In a recent study from our lab, we carried out an analysis with systematic integration of genomic data from mouse models and human HCC tumors and found that APOB ablation in HCC is associated with poor survival of HCC patients. 76 Interestingly, silencing of APOB expression with siRNAs significantly increased cell growth in multiple HCC cells, indicating that APOB may have weak tumor-suppressive activity.…”
Section: Mutational Landscape Of Hccmentioning
confidence: 99%